Pola Pikir dan Pandangan Hidup Masyarakat Masa Lampau dalam Cerita Rakyat di Sepanjang Pesisir Selatan Kabupaten Pacitan - Arif Mustofa; Bakti Sutopo (Jurnal Penelitian Pendidikan, 2013)
As a part of the culture, folklore is important to be documented and studied. The folklore of south coast Pacitan, is still prevalent nowadays. Although it is not all documented, an effort of the research has to be conducted. Beside as an effort of conserving it, the research is also very important to reveal another side of the story. Based on the reason, the study is conducted to reveal the mindset as well as the culture system of the past society reflected in folklore. This study uses the theory of narrative structure of Levi 's Strauss . The method used is a qualitative method approach using anthropology. The data used comes from the 14 folklores taken from the South Coast of Pacitan region. Based on the result of the analysis, it can be concluded that the mindset of the past society can be separated into (1) the social status way, (2) migration way, and (3) the way of techno-economy. While, the life views of the past society in the south coast of Pacitan region are (1) complying the rule, (2) nature as the source of life, and (3 ) Peace of life is very desirable dream.